Persuasive Visual: Body Language and Semantic Relationship Patterns in Press Commercials - Juodytė, Aurelija (Žurnalistikos tyrimai, 2011)
Contemporary popular culture is closely related to visual communication and its standing out phenomenon – advertising. Theorists and various researchers agree about the impact commercials have on individuals, economics, and culture. However, the question, why advertising is so effective even when the message receivers are aware of the deliberate intentions of these communicative items, still has no clear answer. Nationwide it has not been researched yet. The aim of this article is to find out semantic patterns of body language that function as communicative strategies while consuming visual discourse. The semiotic analysis is applied as the research method of commercials. Advertisements from the press that cover women and men magazines, professional and entertainment publications, and national as well as international editions are investigated. Five-year period samples allow to present universal body language use and human body depiction classifications. The main conclusion is that body in visual discourse of commercials is reduced to the instrument of persuasion: body figures simultaneously generate the meaning of the message and inscribe certain values. Because of this constant figurative overshadow and overlap of discursive levels of utterance and annunciation the offering of prescribed benefits and pleasures is so simple and so effective. Keywords: annunciation, advertisement, advertising, body, body language, commercial, decoding, discourse, encoding, meaning, model, pattern, persuasion, press, relationship, semiotics, sense, slogan, strategy, utterance, value, visual.